2007
DOI: 10.1200/jco.2006.08.1935
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate End Points for Median Overall Survival in Metastatic Colorectal Cancer: Literature-Based Analysis From 39 Randomized Controlled Trials of First-Line Chemotherapy

Abstract: In first-line chemotherapy trials for MCRC, improvements in PFS are strongly associated with improvements in OS. In this patient population, PFS may be an appropriate surrogate for OS. As a clinical end point, PFS offers increased statistical power at a given time of analysis and a significant lead time advantage compared with OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
142
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(158 citation statements)
references
References 61 publications
11
142
2
3
Order By: Relevance
“…This issue is even more complicated in international clinical trials when the clinical practice of secondline therapy varies as widely as is seen in advanced gastric cancer. The use of surrogate endpoints, including PFS or time to tumor progression, to evaluate the efficacy of firstline treatment has been extensively studied in trials of colorectal and breast cancers, and data from many metaanalyses indicate that PFS is a good endpoint to evaluate the efficacy of first-line chemotherapy [56][57][58]. Standardization of evaluation of tumor progression is needed to validate the usefulness of these surrogate endpoints in trials of systemic therapy for gastric cancer [59].…”
Section: Discussionmentioning
confidence: 99%
“…This issue is even more complicated in international clinical trials when the clinical practice of secondline therapy varies as widely as is seen in advanced gastric cancer. The use of surrogate endpoints, including PFS or time to tumor progression, to evaluate the efficacy of firstline treatment has been extensively studied in trials of colorectal and breast cancers, and data from many metaanalyses indicate that PFS is a good endpoint to evaluate the efficacy of first-line chemotherapy [56][57][58]. Standardization of evaluation of tumor progression is needed to validate the usefulness of these surrogate endpoints in trials of systemic therapy for gastric cancer [59].…”
Section: Discussionmentioning
confidence: 99%
“…The primary efficacy endpoint was PFS. Because randomized studies with 5-fluorouracil-based chemotherapy have generally demonstrated that longer PFS is accompanied by longer OS, the demonstration of a clinically meaningful longer PFS time in the absence of data suggesting an adverse effect on OS in an adequate and well controlled study would likely have been sufficient to support accelerated approval [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this is likely to impact the choice of primary endpoints for first-line studies in a situation analogous to that seen already in colorectal cancer [69]. It is therefore probable that the use of time to disease progression endpoints as surrogate markers for the survival benefit conferred by new firstline gastric cancer regimens will become more common.…”
Section: Is Second-line Cytotoxic Treatment In Gastric Cancer Likely mentioning
confidence: 99%